ANALISIS MANAJEMEN BERBASIS MADRASAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI MAN 1 JEMBRANA BALI - Maulidiyah, Syifa; Ahmad Tarifin; Siti Nur Azizah; Erni Dina Zuliyanti; Deva Nela Reditha; Salma Bialfi Karimah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was conducted to examine how Madrasah-Based Management (MBM) is implemented to improve the quality of education at MAN 1 Jembrana, Bali. This study covers the application of MBM principles, the role of the madrasah principal and teaching staff, various supporting and inhibiting factors, and strategies implemented to improve the quality of education at the institution. The method used in this research is a qualitative descriptive approach. Data collection was conducted through field observations, document searches, and literature reviews sourced from the official archives of MAN 1 Jembrana, scientific papers, and various other supporting references. The collected data were then analyzed through data reduction, data presentation, and conclusion drawing.The research findings reveal that the implementation of MBM at MAN 1 Jembrana has been quite successful, as evidenced by curriculum management, human resource development, facility and infrastructure arrangement, transparent financial management, the involvement of the madrasah committee and the community, and ongoing monitoring and evaluation activities. This achievement is inseparable from the innovative leadership of the madrasah principal, the professional quality of the teaching staff, the availability of adequate facilities, and a synergistic relationship with the surrounding community. However, this study also identified several challenges, including limitations in some facilities, varying student abilities, the dynamics of constantly changing education policies, and funding constraints. To address these challenges, several strategic steps were implemented, such as strengthening academic supervision, encouraging the digitalization of services, building a culture of literacy, implementing an Internal Quality Assurance System (SPMI), and optimizing the comprehensive implementation of Madrasah-Based Management. These steps are key to driving improvements in educational quality at MAN 1 Jembrana, Bali.